The Effect of Training Methods and Eye-Foot Coordination on the Skills of Dribble, Passing and Football Control - Denny Safarrudin; Setya Rahayu; Sulaiman Sulaiman (STKIP Muhammadiyah Kuningan, 2022)
This study aimed to determine and analyze the effect of passing and dribbling, the impact of high and low eye-foot coordination, the result of passing and dribble control with eye-foot coordination, and the interaction between training methods and eye-eye coordination. Foot on the ability to dribble and control football Quasi-experimental method with 2x2 factorial design. The results of this study: 1) There is a significant difference in the effect of the small-sided game's method with the ladder sprint passing target method on the dribbling, passing and control of SSB Academy R19 Kendal U-15 players in 2022. So that the target practice of passing ladder sprint is better in improving dribbling, skills passing and control. 2) There are significant differences in dribbling, passing and controlling SSB Academy R19 Kendal U-15 players in 2022 who have high and low eye-foot coordination. So high eye-foot coordination is better in improving dribbling, passing and control abilities. 3) There is no significant interaction between training (small-sided game and ladder sprint passing target) and eye-foot coordination on dribbling, passing and control of SSB Academy R19 Kendal U 15 players in 2022.